Peña-Santiago, R. *2006. Book review: GERAERT, E. 2006. Functional and detailed morphology of the Tylenchida (Nematoda). Nematology Monographs and Perspectives, 4: 215 pp. Brill. Leiden, The Netherlands. [ISBN 9004148957] (Journal of Nematode Morphology and Systematics, 2010)
Peña-Santiago, R. *2006. Book review: GERAERT, E. 2006. Functional and detailed morphology of the Tylenchida (Nematoda). Nematology Monographs and Perspectives, 4: 215 pp. Brill. Leiden, The Netherlands. [ISBN 9004148957]